A Case of Medialized Lateral Maxillary Sinus Wall: A Pillar of Support - I. A. Othman; N. D. Hashim; A. J. Nazimi (Case Reports in Medicine)
The number of maxillofacial trauma (MFT) cases attended in the Emergency Department is progressively increasing in trend, owing to the rising statistics of motor-vehicle accidents (MVAs) and urban assaults in addition to occupational-related injuries. Prompt and thorough assessment is important for accurate diagnosis and paramount treatment plans. We will be discussing a case of unusual presentation of an orbital floor fracture post-MVA which was treated conservatively based on the clinical assessments during follow-ups, supported by radiological findings. We will also briefly discuss the different radiological modalities available in assessing MFT and late presentation of enophthalmos.